Aortic Isthmus Narrowing after Endovascular Repair of Acute Traumatic Aortic Transection - Joung Taek Kim (Vascular Specialist International, 2018)
Purpose: The traumatic transection is located in the normal sized aortic isthmus where the angle is curved. We found a reversal of upper and lower blood pressure differences among patients who underwent thoracic endovascular aortic repair (TEVAR) for transection of the thoracic aorta. We investigated the isthmus stenosis in patients who underwent TEVAR for aortic injury using computed tomography.